Clinical and panoramic radiographic features of osteomyelitis of the jaw: A comparison between antiresorptive medication-related and medication-unrelated conditions - Shin, Jeong Won; Kim, Jo-Eun; Huh, Kyung-Hoe; Yi, Won-Jin; Heo, Min-Suk; Lee, Sam-Sun; Choi, Soon-Chul (Imaging science in dentistry, 2019)
This study was performed to analyze the clinical and imaging features of contemporary osteomyelitis (OM) and to investigate differences in these features on panoramic radiography according to patients' history of use of medication affecting bone metabolism. The records of 364 patients (241 female and 123 male, average age 66.8±14.9 years) with OM were retrospectively reviewed. Panoramic imaging features were analyzed and compared between patients with medication-related OM (m-OM) and those with conventional, medication-unrelated OM (c-OM). The age of onset of OM tended to be high, with the largest number of patients experiencing onset in their 70s. The 2 most frequent presumed causes were antiresorptive medication use (44.2%) and odontogenic origin (34.6%). On panoramic radiographs, a mix of osteolysis and sclerosis was the most common lesion pattern observed (68.6%). Sequestrum, extraction socket, and periosteal new bone formation were found in 143 (42.1%), 79 (23.2%), and 24 (7.1%) cases, respectively. The m-OM group exhibited sequestrum and extraction socket more frequently and displayed significantly higher mandibular cortical index values than the c-OM group. We observed some differences in imaging features as shown on panoramic radiography according to the history of antiresorptive medication use. This study may help elucidate the predictive imaging features of medication-related osteonecrosis of the jaw.